2021
DOI: 10.1002/leap.1388
|View full text |Cite
|
Sign up to set email alerts
|

A study of the determinants of psychologists' data sharing and open data badge adoption

Abstract: This research examines whether attitudinal, normative, and behavioural control factors affect psychologists' data sharing and open data badge adoption intentions. The results from the multivariate regression demonstrate that psychologists' (n = 338) data sharing and open data badge adoption intentions are commonly influenced by perceived community benefit, norm of data sharing, and perceived effort involved to share datasets. Additionally, psychologists' data sharing intentions are affected by additional, norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Several studies also concluded that the availability of data repositories can significantly promote scientists’ data sharing behaviours (Kim and Adler, 2015; Kim and Stanton, 2016). For psychologists, in particular, Houtkoop and colleagues (2018) argued that the availability of more data repositories would increase psychologists’ data sharing tendencies; another recent study conducted by Kim (2021) also found that the availability of data repositories in the field of psychology specifically had a significant effect on psychologists’ data sharing intentions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies also concluded that the availability of data repositories can significantly promote scientists’ data sharing behaviours (Kim and Adler, 2015; Kim and Stanton, 2016). For psychologists, in particular, Houtkoop and colleagues (2018) argued that the availability of more data repositories would increase psychologists’ data sharing tendencies; another recent study conducted by Kim (2021) also found that the availability of data repositories in the field of psychology specifically had a significant effect on psychologists’ data sharing intentions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Initial studies in data sharing reported that potential risks of data sharing negatively affected scientists’ data sharing behaviours (Campbell et al , 2002; Louis et al , 2002; Tenopir et al , 2015; Vickers, 2006). However, a series of recent studies found that scientists’ perceived risks in data sharing (as an opposite form of trust) were not a significant factor that prevented them from sharing their data (Kim, 2017, 2021; Kim and Stanton, 2016). Because of this reason, the trust factor in some of the early studies has been replaced by community benefits (Lin and Huang, 2013; Tohidinia and Mosakhani, 2010).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations